Statistical Optimization of Ultra-High-Performance Glass Concrete (2020)
This paper presents the experimental results of research carried out involving the compressive strength and slump flow of ultra-highperformance concrete (UHPC) made with cementitious blends of recycled glass flour, recycled glass powder, micro limestone powder, silica fume, and portland cement. The adopted second-order polynomic regression model provided an accurate correlation between the considered variables and the obtained responses. A numerical optimization was then performed to obtain an eco-friendly mixture with the proper flow, highest compressive strength, and minimum content of cement. The use of 603 kg/m3 of cement in the mixture can be considered as the most appropriate amount to be employed in UHPC mixtures, fulfilling the limit values of compressive strength and spread flow.